Charles de Gaulle - Knapp, Andrew (Abingdon, Oxon ; New York, NY : Routledge, 2021)
In this new biography, Andrew Knapp concisely dissects each of the major controversies surrounding General Charles de Gaulle, leader of the Free French during the Second World War and President of France from 1959 to 1969. From the beginning of de Gaulle's military career in 1909 to an analysis of legacies and myths after his death in 1970, this study examines the path by which the French came to honour him as the greatest Frenchman of all time, and as the twentieth century's pre-eminent world statesman. In each chapter, Knapp analyses de Gaulle's participation in key events such as the development of France's resistance against Nazi Germany, the decolonisation of Algeria, the birth of the French Fifth Republic, and the gigantic upheaval of May 1968. Simultaneously, this study questions de Gaulle's actions and motives throughout his life. By exploring the justification of the contemporary de Gaulle myth', Knapp concludes by shedding new light on the influence of de Gaulle in the political culture of twenty-first-century France. Through careful analysis of primary sources as well as recent scholarship, this biography is an invaluable source for scholars and students of modern history, the history of France, political institutions, and international relations.
OCLC-licensed vendor bibliographic record.
Keywords: Gaulle, Charles de, -- 1890-1970.; Presidents -- France -- Biography; Generals -- France -- Biography; Statesmen -- France -- Biography; France -- Politics and government -- 20th century; HISTORY / Europe / France; HISTORY / Modern / 20th Century; HISTORY / Military / World War II